Using the Deep Constrained Clustering Approach to Create a Business Profile - Latif, Abdul; Sutarman; Damius, Open (Sinkron : jurnal dan penelitian teknik informatika, 2022)
Identification of customers in the business sector that really needs to be done as an evaluation of a business that is run so that it can continue to grow and be able to follow business developments in the same sector. The deep constraint clustering approach is used to cluster customers towards a business. In this study, a clustering of customers using rail mass transportation will be carried out. The results achieved are the formation of 6 clusters using trains be built. The result of research expected to be a consideration in improving services to the company